School Policy In the Development of the Islamic Religious Education Curriculum: A Case Study at SMAS YPPL Panjang - Kesuma, Muhammad Ilham Jaya; Sari, Indah Nur Bella; Yansyah, M. Eko Juli; Sari, Misalia; Anwar, Chairul; Anwar, Syaiful; Dacholfany, Muhammad Ihsan (IAIN KENDARI, 2025)
This study aims to analyze the policies implemented by schools in developing the Islamic Religious Education curriculum at SMAS YPPL Panjang, so that the curriculum is more relevant to the needs of students in the current digital era. In the context of globalization and digitalization, the challenges faced in developing the Islamic Religious Education curriculum are increasingly complex. For this reason, this study uses a qualitative method with a case study approach. Data were collected through in-depth interviews, observations, and document analysis. The results of the study indicate that school policies include several strategic steps, including increasing the effectiveness of teacher training to overcome resource limitations, strengthening facilities and infrastructure that support experience-based learning, and utilizing social media as a digital da'wah tool to respond to the influence of pop culture on students. In addition, the involvement of parents and the community is also an important aspect in the school's strategy to strengthen students' understanding of Islamic Religious Education and shape their Islamic character